Subcortical brain trajectories in later life between sexes and APOE genotypes: A UK Biobank study of individuals of self‐identified Indian ancestry. (1st February 2022) - Muir, Alexandra M; Ching, Christopher; Santhalingam, Vigneshwaran; Abaryan, Zvart; Zhu, Alyssa H; John, John P; Venkatasubramanian, Ganesan; Thomopoulos, Sophia I; Jahanshad, Neda; Thompson, Paul M
Abstract: Background: In the UK, individuals with Indian ancestry show lower rates of dementia compared to other ethnicities. Most dementia studies mainly examine individuals of European ancestry and/or higher socioeconomic status, making it unclear if effects generalize to other populations. Here we map age trends in subcortical brain morphometry in later life and investigate the modulating effects of sex and APOE genotype in people of self‐identified (SI) Indian ancestry. Method: T1‐weighted MRI scans from mostly healthy individuals with SI‐Indian ancestry from the UK Biobank (; N = 297; born in India = 43.1%) were processed using FreeSurfer v7.1 to derive bilaterally averaged hippocampus, thalamus, putamen, pallidum, amygdala, caudate, nucleus accumbens, and ventricle volumes. SI‐ancestry groups were confirmed with the first three genetic principal components ()4. Sex‐stratified normative centile reference curves (nomograms) of standardized residuals corrected for intracranial volume (ICV) and scanner were plotted for each structure. Linear mixed models were used to investigate a sex‐by‐age interaction adjusted for scanner and ICV. APOE ε4 carriers and non‐carriers were compared. All results were corrected for multiple comparisons. Result: Nomograms () show a similar pattern for SI‐Indian and SI‐European ancestry groups (N= 35, 608). All subcortical volumes generally declined significantly with increasing age, except for the ventricles which increased as expected ( ; Cohen's d : 0.12 ‐ 0.93). No subcortical region showed a significant age by sex interaction (). Subcortical volumes did not differ between carriers and non‐carriers (). Conclusion: Nomograms and statistical analysis of subcortical brain volume trajectories showed similar patterns between SI‐Indian and SI‐European groups. In the current sample, we detected no sex by age interaction for any subcortical volume nor detrimental effect of APOE ε4 allele, likely due to lack of power. Larger samples of SI‐Indian ancestry individuals along with analyses accounting for life expectancy, short survival with dementia, and risk/protective factors compared with populations of higher prevalence will be valuable to assess whether differential subcortical trajectories may account for lower rates of AD in India compared to other countries.